2007
DOI: 10.1007/bf03349224
|View full text |Cite
|
Sign up to set email alerts
|

Physiological dose of lycopene suppressed oxidative stress and enhanced serum levels of immunoglobulin M in patients with Type 2 diabetes mellitus: A possible role in the prevention of long-term complications

Abstract: Lycopene, probably by increasing TAC and inhibiting MDA-LDL formation, may attenuate T cell-dependent adaptive (pro-atherogenic) immune response. Meanwhile, with enhancement of innate immunity and hence prevention of ox-LDL uptake by macrophage and foam cell formation, lycopene may be effective in prevention of long-term diabetic complications, notably cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 33 publications
0
54
0
4
Order By: Relevance
“…This stimulation of lycopene on IgG production has been observed in other studies, like that carried out by Luo and Wu (2011), showing that lycopene can increase blood levels of IgA, IgG and IgM, improving the immunity of rats with cancer. Similarly, Neyestani et al (2007) observed that dietary supplementation of lycopene stimulates the formation of specific antibodies, mainly IgG isotype, reporting that lycopene is not only a common immune enhancer, because it provides an specific immune stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…This stimulation of lycopene on IgG production has been observed in other studies, like that carried out by Luo and Wu (2011), showing that lycopene can increase blood levels of IgA, IgG and IgM, improving the immunity of rats with cancer. Similarly, Neyestani et al (2007) observed that dietary supplementation of lycopene stimulates the formation of specific antibodies, mainly IgG isotype, reporting that lycopene is not only a common immune enhancer, because it provides an specific immune stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, b-carotene bioavailability is maintained with age, as is the intestinal conversion of PVA carotenoids to vitamin A. Recently, a double-blind placebo-controlled clinical trial found a physiological dose of lycopene for 2 months suppressed oxidative stress and enhanced innate immunity in individuals with type 2 diabetes (24) . We also observed an association between retinopathy and plasma PVA carotenoid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, because lycopene, an antioxidant substance in the carotenoid family of compounds, can mitigate/abrogate oxidative stress (see most recent of > 200 papers on subject, i.e., Attesahin et al, 2007;Bose and Agrawal, 2007;Neyestani et al, 2007)-including that induced by mercury (Augusti et al, 2007)-it is likely that this effect is an important factor in the keratinocytes' renewed ability to establish GJIC and undergo inducible cytokine formation that had been reduced by mercury. Further studies by our research group will better clarify the mechanisms by which lycopene had the effects shown here and determine if these can be replicated with other known toxicants, particularly carcinogens.…”
Section: Discussionmentioning
confidence: 99%